Implementation of blinded outcome assessment in the Effective Verruca Treatments trial (EverT) – lessons learned. Issue 1 (December 2016) - Cockayne, Sarah; Hewitt, Catherine; Hashmi, Farina; Hicks, Kate; Concannon, Michael; McIntosh, Caroline; Thomas, Kim; Hall, Jill; Watson, Judith; Torgerson, David; Watt, Ian
Abstract Background Trials using inadequate levels of blinding may report larger effect sizes than blinded studies. It has been suggested that blinded outcome assessment in open trials may in some cases be undertaken by assessments of photographs. The aim of this paper is to explore the effect of using different methods to assess the primary outcome in the EVerT (Effective Verruca Treatments) trial. It also aims to give an overview of the experiences of using digital photographs within the trial. Methods We undertook a secondary analysis to explore the effect of using three different methods to assess the primary outcome in the EVerT trial: assessment of digital photographs by blinded healthcare professionals; blinded healthcare professional assessment at the recruiting site and patient self-report. The verruca clearance rates were calculated using the three different methods of assessment. A Cohen's kappa measure of inter-rater agreement was used to assess the agreement between the methods. We also investigated the experiences of healthcare professionals using digital photographs within the trial. Results Digital photographs for 189 out of 240 (79 %) patients in the trial were received for outcome assessment. Of the 189 photographs, 30 (16 %) were uninterpretable. The overall verruca clearance rates were 21 % (43/202, ) using the unblinded patient self-reported outcome, 6 % (9/159, ) using blinded assessment of digital photographs and 14 % (30/210, ) using blinded outcome assessment at the site. Conclusions Despite differences in the clearance rates found using different methods of outcome assessment, this did not change the original conclusion of the trial, that there is no evidence of a difference in effectiveness between cryotherapy and salicylic acid. Future trials using digital photographs should consider individual training needs at sites and have a backup method of assessment agreeda priori . Trial registration ISRCTN RegistryISRCTN18994246